Therapeutic effects and mechanism of Atractylodis rhizoma in acute lung injury: Investigation based on an Integrated approach - Shi, Kun; Wang, Yan; Xiao, Yangxin; Tu, Jiyuan; Zhou, Zhongshi; Cao, Guosheng; Liu, Yanju (Frontiers in Pharmacology, 2023)
Acute lung injury (ALI) is characterized by an excessive inflammatory response. Atractylodes lancea (Thunb.) DC. as a traditional Chinese medicine with good anti-inflammatory activity that is commonly used clinically for the treatment of lung diseases in China. However, its mechanism of against acute lung injury is unclear.We clarified the therapeutic effects of EEAR on lipopolysaccharide (LPS)-induced ALI by evaluation of hematoxylin-eosin (HE) stained sections, the lung wet/dry (W/D) ratio, and levels of inflammatory factor as indicators. We then characterized the chemical composition of EEAR by UPLC-MS and screened the components and targets by network pharmacology to clarify the signaling pathways involved in the therapeutic effects of EEAR on ALI, and the results were validated by molecular docking simulation and Western blot (WB) analysis. Finally, we examined the metabolites in rat lung tissues by GC-MS. The results showed that EEAR significantly reduced the W/D ratio, and TNF-α, IL-1β, IL-6 levels in the lungs of rats with ALI. Nineteen components of EEAR were identified and shown to act synergetically by regulating shared pathways such as the mitogen-activated protein kinase (MAPK) and phosphoinositide 3-kinase (PI3K)-protein kinase B (AKT) signaling pathways. Ferulic acid, 4-methylumbelliferone, acetylatractylodinol, atractylenolide I, and atractylenolide III were predicted to bind well to PI3K, AKT and MAPK1, respectively, with binding energies <-5 kcal/mol, although only atractylenolide II bound with high affinity to MAPK1. EEAR significantly inhibited the phosphorylation of PI3K, AKT, p38, and ERK1/2, thus reducing protein expression. EEAR significantly modulated the expression of metabolites such as D-galactose, D-glucose, serine and D-mannose. These metabolites were mainly concentrated in the galactose and amino acid metabolism pathways. In a conclusion, EEAR alleviates ALI by inhibiting activation of the PI3K-AKT and MAPK signaling pathways and regulating galactose metabolism, providing a new direction for the development of drugs to treat ALI.